Takotsubu Cardiomyopathy Patient With Coronary Artery Disease: The Chicken or the Egg - Chara Ude; Ayman Helal; Ibrahim Antoun (Clinical Case Reports)
ABSTRACT This case emphasizes the rare occurrence of Takotsubo cardiomyopathy (TTC) in a patient with moderate coronary artery disease (CAD), highlighting the complexity of diagnosis and management. Clinicians should maintain a high index of suspicion for TTC in patients with CAD, especially when echocardiographic findings suggest apical ballooning. Balancing therapies for both conditions is essential.